Agricultural constraints on microbial resource use and niche breadth in drainage ditches - Ellard R. Hunting; S. Henrik Barmentlo; Maarten Schrama; Peter M. van Bodegom; Yujia Zhai; Martina G. Vijver (PeerJ, 2017)
Background Microorganisms govern important ecosystems processes, in particular the degradation of organic matter (OM). However, microorganisms are rarely considered in efforts to monitor ecosystem health and functioning. Evidence suggests that environmental perturbations can adversely affect microbial communities and their ability to use available substrates. However, whether impacted microbial efficiencies in extracting and utilizing the available resources (resource niche breadth) translate to changes in OM degradation in natural systems remains poorly understood. Methods Here we evaluated effects of differences in OM related to agricultural land use (OM derived from ditches adjacent to grasslands, bulb fields and a pristine dune area) on microbial functioning. We specifically assessed (1) resource niche breadths of microbial communities during initial community assembly in laboratory microcosms and already established natural communities, and (2) how changes in community resource niche breadth translates to the degradation of natural OM. Results A disparity existed between microbial resource niche breadth in laboratory incubations and natural microbial communities. Resource utilization and niche breadth of natural microbial communities was observed to be constrained in drainage ditches adjacent to agricultural fields. This outcome coincides with retarded degradation of natural OM collected from ditches adjacent to hyacinth bulb fields. Microbial communities in bulb field ditches further showed functional redundancy when offered grassland OM of seemingly higher substrate quality. Discussion Results presented in this study suggest that agricultural practices can impose constraints on microbial functional diversity by reducing OM resource quality, which can subsequently translate to confined microbial resource niche differentiation and reduced organic matter degradation rates. This hints that assessments of actual microbial resource utilization and niche differentiation could potentially be used to assess the ecological health and functioning of natural communities.